Power transfer capability enhancement with multitype FACTS controllers using hybrid particle swarm optimization - Suppakarn Chansareewittaya (2018)
© 2014, Springer-Verlag Berlin Heidelberg. In this paper, a new hybrid particle swarm optimization (HPSO) based on particle swarm optimization (PSO), evolutionary programming (EP), tabu search (TS), and simulated annealing (SA) is proposed. The aim of merging is to determine the optimal allocation of multi-type flexible AC transmission system (FACTS) controllers for simultaneously maximizing the power transfer capability of power transactions between generators and loads in power systems without violating system constraints. The particular optimal allocation includes optimal types, locations, and parameter settings. Four types of FACTS controllers are included: thyristor-controlled series capacitor, thyristor-controlled phase shifter, static var compensator, and unified power flow controller. Power transfer capability determinations are calculated based on optimal power flow (OPF) technique. Test results on IEEE 118-bus system and Thai Power 160-Bus system indicate that optimally placed OPF with FACTS controllers by the HPSO could enhance the higher power transfer capability more than those from EP, TS, and hybrid TS/SA. Therefore, the installation of FACTS controllers with optimal allocations is beneficial for the further expansion plans.